2002
DOI: 10.1097/00000658-200212000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated Single Tumor Cells as Detected by Real-Time Quantitative Polymerase Chain Reaction Represent a Prognostic Factor in Patients Undergoing Surgery for Colorectal Cancer

Abstract: These data suggest that detection of mRNA coding for CEA and/or CK20 using qPCR has potential clinical utility as a prognostic marker and should be evaluated in larger clinical studies. Identification of patients at high risk for metastatic disease after curative resection of colorectal cancer might be improved by analyzing peritoneal lavage specimens in addition to blood samples. This is based on the observation that in more than half of qPCR-positive patients, disseminated colorectal cancer cells were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
98
0
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(109 citation statements)
references
References 40 publications
4
98
0
7
Order By: Relevance
“…Eight studies were excluded as they reported only on preoperative blood sampling (Bessa et al, 2001;Fujita et al, 2001;Wong et al, 2001;Zhang et al, 2005;Douard et al, 2006;Iinuma et al, 2006;Wang et al, 2006;Friederichs et al, 2007). Nine studies were excluded as they contained data from which outcomes could not be extracted, of which four were excluded as they combined positive results of molecular detection of multiple samples and their effect on prognosis (Hardingham et al, 2000;Guller et al, 2002;Bosch et al, 2003;Koyanagi et al, 2008), and five were excluded as it was impossible to extract the data for outcomes of interest (White and Griffiths, 1976;Funaki et al, 1998;Wyld et al, 1998;Conzelmann et al, 2005;Wang et al, 2007). Five studies were excluded as they were reviews or systematic reviews, which did not report on prognostic outcomes (Tsavellas et al, 2001;Sleijfer et al, 2007;Riethdorf et al, 2008;Sergeant et al, 2008;Tsouma et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies were excluded as they reported only on preoperative blood sampling (Bessa et al, 2001;Fujita et al, 2001;Wong et al, 2001;Zhang et al, 2005;Douard et al, 2006;Iinuma et al, 2006;Wang et al, 2006;Friederichs et al, 2007). Nine studies were excluded as they contained data from which outcomes could not be extracted, of which four were excluded as they combined positive results of molecular detection of multiple samples and their effect on prognosis (Hardingham et al, 2000;Guller et al, 2002;Bosch et al, 2003;Koyanagi et al, 2008), and five were excluded as it was impossible to extract the data for outcomes of interest (White and Griffiths, 1976;Funaki et al, 1998;Wyld et al, 1998;Conzelmann et al, 2005;Wang et al, 2007). Five studies were excluded as they were reviews or systematic reviews, which did not report on prognostic outcomes (Tsavellas et al, 2001;Sleijfer et al, 2007;Riethdorf et al, 2008;Sergeant et al, 2008;Tsouma et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Viable cancer cells can be recovered from surgical sites, the lymphatics, and venous circulation during both tumor resection and metastasis (21,22,55,62). The formation of secondary tumors requires the adhesion of these cells to surrounding tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, CEA has been reported to be a reliable target for the detection of disseminated gastric cancer cells, and is the most common marker for detecting micrometastasis with RT -PCR (Kodera et al, 1998;Nakanishi et al, 2000;Osaka et al, 2004). The quantitative RT -PCR method using multiple markers reportedly improved the sensitivity and specificity of the quantitative RT -PCR method (Guller et al, 2002;Timar et al, 2002;Osaka et al, 2004;Fujita et al, 2006). We therefore selected the combination of CEA and CK-20 as diagnostic markers for predicting micrometastasis in patients with gastric carcinoma in this study.…”
Section: Discussionmentioning
confidence: 99%